2016
DOI: 10.1063/1.4962498
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscopy and field emission schemes for studying electron emission from polycrystalline diamond

Abstract: The letter introduces a diagram that rationalizes tunneling atomic force microscopy (TUNA) observations of electron emission from polycrystalline diamonds as described in recent publications [1,2]. The direct observations of electron emission from grain boundary sites by TUNA could indeed be evidence of electrons originating from grain boundaries under external electric fields. At the same time, from the diagram it follows that TUNA and field emission schemes are complimentary rather than equivalent for result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, it should be mentioned that many different groups have worked on the local EFE behavior of UNCD films and observed that electrons were primarily emitted from the grain boundaries amidst the asperities of diamond surfaces. This occurs because the electrons, which were supplied by the bottom external electrodes (through the substrates), were transported along the path with the smallest resistance in the diamond materials upward to the top surface of the UNCD films and were then emitted there.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, it should be mentioned that many different groups have worked on the local EFE behavior of UNCD films and observed that electrons were primarily emitted from the grain boundaries amidst the asperities of diamond surfaces. This occurs because the electrons, which were supplied by the bottom external electrodes (through the substrates), were transported along the path with the smallest resistance in the diamond materials upward to the top surface of the UNCD films and were then emitted there.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the localized FEE properties of the BNCD–CNSs hybrids were also investigated by the AFM-based PF-TUNA technique so as to directly locate the precise electron emission sites locally to understand the role of the BNCD and the CNSs materials on improving the FEE characteristics. Figure a shows the AFM surface morphology along with the representing PF-TUNA current mapping image (Figure b) of the BNCD films.…”
Section: Resultsmentioning
confidence: 99%